Plan de marketing de comercialización de escritorios de cartón - Alcoser Kok, Sebastián Stéfano (2021)
On this paper, the business plan for cardboard desk in Lima Metropolitana will be presented as a product that is currently not found in our country. We will seek to show the viability of this innovative product, as well as the evaluation of the current furniture market in the country. The desk will be made from recycled cardboard and sold through an own e-commerce platform, seeking to obtain a WIN WIN WIN since we will have social impact strategies such as the use of recycled products and alliances with suppliers. The target audience for the product are young adults residing in Metropolitan Lima, who seek to optimize the spaces in their home and have a high sensitivity for the environment.